Inlet Pressure Effects on Subatmospheric Flame Stabilization with an Optimum Size of a Cavity-Based Combustor - Yakun Huang; Xiaomin He; Zhixin Zhu; Huanyu Zhu (International Journal of Aerospace Engineering)
Experimental studies are conducted to find an optimum size of the cavity flameholder, which is a new combustion concept of a turbine-based combined-cycle (TBCC) engine with an excellent flame stabilization. Besides, the effect of inlet pressure on the subatmospheric performance is investigated. The experimental results indicate that the increase of the cavity length improves the flame stability with an enlarged fuel/air mixture residence time, which suggests that the big length-height ratio in a proper range of the cavity with a stable dual-vortex should be chosen when designing the cavity-based combustor. In addition, the decrease in lean ignition and the lean blowout equivalence ratios can be attributed by either increase in the inlet pressure and temperature or decrease in the Mach number. The increase in inlet pressure will lead to a linear decrease in the lean blowout equivalence ratio with a slope of 0.66 per 0.1 MPa, whereas the lean ignition equivalence ratio has a rapid drop with the increase of pressure from 0.06 MPa to 0.08 MPa and reduces slowly with the growth of pressure in the range of 0.08 MPa to 0.1 MPa. The detailed analysis of the flow field indicates that the characteristic time-scale theory can ideally explain and predict the change of flame stability in the trapped vortex cavity.